Search for single production of scalar leptoquarks in p(p)over-bar collisions decaying into muons and quarks with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2007)
lWe report on a search for second generation leptoquarks (LQ(2)) which decay into a muon plus quark in (p) over barp collisions at a center-of-mass energy of root s = 1.96 TeV in the DO detector using an integrated luminosity of about 300 pb(-1). No evidence for a leptoquark signal is observed and an upper bound on the product of the cross section for single leptoquark production times branching fraction into a quark and a muon was determined for second generation scalar leptoquaiks as a function of the leptoquark mass. This result has been combined with a previously published DO search for leptoquark pair production to obtain leptoquark mass limits as a function of the leptoquark-muon-quark coupling, lambda. Assuming lambda = 1, lower limits on the mass of a second generation scalar leptoquark coupling to a u quark and a muon are m(LQ2) > 274 GeV and m(LQ2) > 226 GeV for beta = 1 and beta = 1/2, respectively. (c) 2007 Elsevier B.V. All rights reserved.